2018
DOI: 10.1080/13218719.2018.1485523
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based psychosocial treatments of conduct problems in children and adolescents: an overview

Abstract: The aims of the present study were to identify empirically supported psychosocial intervention programs for young people with conduct problems and to evaluate the underpinnings, techniques and outcomes of these treatments. We analyzed reviews and meta-analyses published between 1982 and 2016 concerning psychosocial intervention programs for children aged 3 to 12 years with conduct problems. Parent training should be considered the first-line approach to dealing with young children, whereas cognitivebehavioral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 110 publications
1
9
0
Order By: Relevance
“…In addition to the treatment, the AUHARK smartphone app will be used in the experimental group. The treatment will be administered in three phases (1)(2)(3). Each phase includes eight weekly therapy sessions with the children and two to three sessions with the parents/ caregivers.…”
Section: Trial Designmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the treatment, the AUHARK smartphone app will be used in the experimental group. The treatment will be administered in three phases (1)(2)(3). Each phase includes eight weekly therapy sessions with the children and two to three sessions with the parents/ caregivers.…”
Section: Trial Designmentioning
confidence: 99%
“…Various interventions have been proven to be effective for the treatment of children and adolescents with oppositional defiant disorder (ODD) and conduct disorder (CD). In particular, studies have demonstrated the effectiveness of child-focused interventions (social competence training), parent-focused interventions (parent management training), combined child-parent interventions, and multimodal or multi-component programs [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…As stated above, our study cannot prove effectiveness of counselling in reducing exclusion, but merely suggest it as a possibility. In addition, we can only hypothesise the mechanisms by which attendance at individual counselling might produce improvements in exclusion, particularly as there is little supporting evidence of individual counselling having a direct influence on classroom behaviour (Gatti, Grattagliano, & Rocca, 2019). The presence of a mental health service in school could help staff to understand and be more aware of mental health difficulties that children and young people experience (Banerjee, Mclaughlin, Cotney, Roberts, & Peereboom, 2016).…”
Section: Possible Explanationsmentioning
confidence: 99%
“…The onset of CD in childhood is associated with poor outcomes in adulthood, such as an increase in criminal behavior, violence, and progression to antisocial behavior. Children with CD are also at an increased risk for substance use disorders (SUD) and personality disorders such as antisocial personality disorder [16]. Neuroimaging studies in children with CD revealed a smaller size of the amygdala, the insula, the ventromedial prefrontal cortex, and the orbitofrontal cortex.…”
Section: Conduct Disordermentioning
confidence: 99%